Focus point: History - The politics of energy in Africa : Energy partnership with Africa burdens of history and current perspectives - Speitkamp, Winfried; Stange, Daniel; Justus Liebig University Giessen (My University, 2008)
He who wants to shape the future must understand the past. Nowhere this is as much the case as in the relationship between Europe and Africa. An energy partnership with Africa means that on the one hand the specifichistory that connects Africa with Europe must be recognized, and the burdens of the shared history must be given consideration. On the other hand the interests of the African states must be identified, for example, which energy policy is being pursued and which energy conflicts are being carried out.
Keywords: ddc:330